Front Cover: Structure‐Performance Guided Design of Sustainable Plasticizers from Biorenewable Feedstocks (Eur. J. Org. Chem. 45/2021). Issue 45 (29th November 2021) - Plass, Carmen; Adebar, Niklas; Hiessl, Robert; Kleber, Joscha; Grimm, Axel; Langsch, Angelika; Otter, Rainer; Liese, Andreas; Gröger, Harald
Abstract : The Front Cover illustrates a concept to switch the raw material basis for plasticizer production from fossil to bio‐based feedstocks. The bicyclic plasticizers, which were synthesized as target molecules, are accessible from bio‐based 2‐methylfuran, maleic anhydride and 2‐ethylhexanol. Evaluating the performance of this new bio‐based plasticizer generation revealed promising plasticizing properties. More information can be found in the Full Paper by R. Otter, A. Liese, H. Gröger et al .